"Shall I compare thee to a summer's day?": intralocution and the teaching of Renaissance poetry in Taiwan - Yang, Chih-chiao Joseph (2006)
This thesis examines the educational role of English literature in Taiwan and proposes a method of reading and teaching English Renaissance poetry for Taiwanese students and teachers. Based upon the idea of integrating literature and language, this thesis suggests a stylistic approach to reading as well as interpreting literary texts.